Profitable online human resource (HR) businesses. - Chew, Wei Ting. (2008)
Many companies are struggling with the most basic problem: the best approach for establishing and doing business in the digital economy. The result of our analysis shows that online human resource (HR) consulting service is the most feasible and prospective form of HR Internet business.